Plant Growth Promoting Actinobacteria 2016
DOI: 10.1007/978-981-10-0707-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plant Growth-Promoting Actinomycetes on Vigna

Abstract: The legume genus Vigna are grown in warm temperate and tropical regions globally but are particularly crucial to human nutrition in large parts of tropical Africa and Asia. It can also serve as forage crops. Among the Vigna species, the Asian Vigna has received little research initiatives than African Vigna such as cowpea and mung bean. From the last decade, the research initiatives are getting increased for both the Vigna species in the context of genetic resource analysis and genome mapping. The production s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…reported that the application of 20 kg K/ ha plus 15 kg Fe/ha produces an optimum level of plant parameters encompassing plant height, nodules per plant, plant dry weight, branches per plant, pods per plant, and seeds per pod.During an investigation on rice beans,Susilowati et al (2016) reported that the combination of 5 Mg organic fertilizer, 50% of recommended fertilizer, plus MVA induces the productivity and quality of the rice bean crop. Furthermore,Ponmurugan et al (2016) also documented that using plant growth-promoting microbes, particularly actinomycetes, increases the growth performance and production ability in Vigna by boosting nitrogen availability and metabolism. Similarly, the result obtained in this research corresponds with the findings ofBehera et al (2017), who reported that applying a successive dose of nitrogen up to 40 kg/ha produces the maximum yield attributing characters, including the clusters per plant and pods per plant.…”
mentioning
confidence: 97%
“…reported that the application of 20 kg K/ ha plus 15 kg Fe/ha produces an optimum level of plant parameters encompassing plant height, nodules per plant, plant dry weight, branches per plant, pods per plant, and seeds per pod.During an investigation on rice beans,Susilowati et al (2016) reported that the combination of 5 Mg organic fertilizer, 50% of recommended fertilizer, plus MVA induces the productivity and quality of the rice bean crop. Furthermore,Ponmurugan et al (2016) also documented that using plant growth-promoting microbes, particularly actinomycetes, increases the growth performance and production ability in Vigna by boosting nitrogen availability and metabolism. Similarly, the result obtained in this research corresponds with the findings ofBehera et al (2017), who reported that applying a successive dose of nitrogen up to 40 kg/ha produces the maximum yield attributing characters, including the clusters per plant and pods per plant.…”
mentioning
confidence: 97%